USING DIGITAL STORY TELLING TO IMPROVE STUDENTS’ SPEAKING ABILITY IN SENIOR HIGH SCHOOL - Ridhwan Yusuf; Desvalini Anwar (Journal of English Language Teaching, 2018)
The use of technology in the term of teaching is really helpful. The use of technique with technology based in teaching English is expected to improve the ability of students in learning English. Speaking is one of the basic ability which is not easy to master without appropriate technique. One of the obstacles for students in speaking English is students are lack of understanding of what they say, so they do not really comprehend speaking skill thoroughly. Storytelling is one of the techniques that is commonly used in teaching English. With the use of technology, storytelling can be digital storytelling. Digital storytelling is a storytelling that is produced in the form of video. In this paper, students are asked to make a story about his friend, which is the final result is in the form of video. In its stages, firstly, students are asked to make a draft about the video they are going to make. After completing the draft, students continue to the next stage which is editing the video. It consists of music background, quotes, the voice over, or also pictures. By implementing this technique, students are expected can improve their speaking skill in learning English.